Magmatic switch-on and switch-off along the South China continental margin since the Permian: Transition from an Andean-type to a Western Pacific-type plate boundary - Li, Zheng-Xiang; Li, X.; Chung, S.; Lo, C.; Xu, X.; Li, W. (Elsevier Science BV, 2012)
Detrital zircon provenance data for the Tananao schist in eastern Taiwan is consistent with its protolith being deposited on the South China continental margin at around, or soon after, 150 Ma, rather than being of an exotic origin and much older as previously suggested. The absence of ca. 200 Ma zircons agrees with the presence of a magmatic gap in the region after the orogenic and magmatic front migrated to central South China, due to a flat-slab subduction. The characteristic lack of input from interior South China (i.e., the lack of 1100–750 Ma and 470–420 Ma populations), and the immature nature of some of the schist units, suggest that they were sourced from the nearby coastal regions. On the other hand, they exhibit a dominant 190–150 Ma magmatic zircon population, suggesting the presence of abundant magmatic rocks of that age along the coastal regions. This, along with our newly discovered ca. 180 Ma I-type granites from eastern Zhejiang and other ca. 190–180 Ma magmatic rocks recently reported from the coastal regions, led us to propose that a new continental arc was initiated after ca. 190 Ma along the coastal region after a magmatic gap due to flat-slab subduction. This newly initiated arc likely persisted until ca. 90 Ma, and is represented by the I-type granitic rocks in eastern Taiwan. Slab roll-back likely caused the arc system to retreat towards the Pacific Ocean after 90 Ma, and ca. 60–17 Ma bimodal magmatism adjacent to the South China Sea signifies continental margin extension in the lead-up to, and during, the opening of the South China Sea. We thus argue that the continental margin of East Asia was transformed from an Andean-type plate margin at 280–90 Ma, to the present-day Western Pacific-type plate margin soon after 90 Ma.